2022
DOI: 10.1039/d2tc03239b
|View full text |Cite
|
Sign up to set email alerts
|

Soft, flexible and self-healable supramolecular conducting polymer-based hydrogel electrodes for flexible supercapacitors

Abstract: Conducting polymer-based hydrogels have drawn great attention recently as stretchable, soft electrode materials for flexible supercapacitors, for wearable electronics applications. In this work, we strategically combined the supramolecular approach and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…15 Moreover, a characteristic crystallization peak at 2 θ = 25.6° could be observed, which was assigned to the amorphous structure of PANI chains in PP hydrogels. 45 For PHP hydrogels, typical peaks of PVA and PANI also appeared. However, the diffraction peak of HQ could hardly be observed (the standard PDF card# 48-2239 of HQ was given in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Moreover, a characteristic crystallization peak at 2 θ = 25.6° could be observed, which was assigned to the amorphous structure of PANI chains in PP hydrogels. 45 For PHP hydrogels, typical peaks of PVA and PANI also appeared. However, the diffraction peak of HQ could hardly be observed (the standard PDF card# 48-2239 of HQ was given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The most common conductive polymer hydrogels include polyaniline (PANI), 8,9 polypyrrole (PPy), 10,11 and polythiophene (PTh) 12,13 hydrogels. For instance, Bao et al 14 synthesized a PANI hydrogel via direct polymerization of aniline monomers with phytic acid as the dopant.…”
Section: Introductionmentioning
confidence: 99%
“…4f), which is much larger than the state of the art. [51][52][53] It maintains 495 mF cm À2 at 5 mA cm À2 , which is still 2.8 times larger than that of the PEDOT/PAA electrode (176 mF cm À2 ). The remarkable enhancement in electrochemical capacitance value could be related to the permanent doping state of AQS on the PEDOT chains due to its large size and steric hindrance (Fig.…”
Section: Capacitance Performance Of the Diverse Aqs-pedot/paa Electrodesmentioning
confidence: 88%
“…For future work to be successful, a re-imagining of the resin will need to be performed with a key focus placed on preventing cross-contamination between the materials over time. Recent conducting polymer research has revealed a potential solution to these issues (Zhu et al , 2022). By grafting cross-linkable pendant chains onto the conducting polymer backbone, crosslinked sections can be added and prevent cross-contamination of layers and increase conductivity.…”
Section: Discussionmentioning
confidence: 99%